2018
DOI: 10.1021/acssuschemeng.8b04382
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Derived Porous Carbon Loaded with La(OH)3 Nanorods for Highly Efficient Removal of Phosphate

Abstract: Removing phosphate ions from eutrophic waters is of paramount importance; however, the design of low-cost, high-performance adsorbents for phosphorus removal has remained a huge challenge. Herein, we have demonstrated the fabrication of a low-cost, eco-friendly absorbent, LPC@La­(OH)3, by loading lanthanum hydroxide nanorods within lignin-derived porous carbon for superfast and highly efficient phosphorus removal. As-prepared LPC@La­(OH)3 exhibits a high adsorption capacity of 60.24 mg P L–1 and a high lanthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…1 eV) and sharply decreased intensity for La 3d after adsorption were also noted, indicating the formation of La-O-As complexes (Fig. 6c) [2,44]. Meanwhile, the neglected effect of ionic strength on arsenate removal further confirmed the formation of an inner sphere complex M−O−As (M = La, Mn) [44] (Fig.…”
Section: Arsenate Removal At Low As(v)/ Mnl Ratiomentioning
confidence: 79%
“…1 eV) and sharply decreased intensity for La 3d after adsorption were also noted, indicating the formation of La-O-As complexes (Fig. 6c) [2,44]. Meanwhile, the neglected effect of ionic strength on arsenate removal further confirmed the formation of an inner sphere complex M−O−As (M = La, Mn) [44] (Fig.…”
Section: Arsenate Removal At Low As(v)/ Mnl Ratiomentioning
confidence: 79%
“…The infrared absorption spectra of the uncured solid epoxy resin (EP), EHTPB, and cured EHTPB‐modified epoxy resin (EP/EHTPB) are shown in Figure (b). For the spectrum of EP and EP/EHTPB, the wideband located at 3340 cm −1 corresponds to the symmetric stretch vibration of ‐OH, and the peaks at 2964 cm −1 , 2928 cm −1 , and 2870 cm −1 can be attributed to the stretching of the unsaturated −CH and saturated −CH, respectively . The typical absorption bands of benzene appeared around 1607 cm −1 and 1508 cm −1 , and no significant difference was obtained during curing.…”
Section: Resultsmentioning
confidence: 96%
“…Lanthanum-modified biochar is a type of soil adsorbent having stable properties, pH independency, wide range of sources, low cost, and low environmental risk (Copetti et al 2015;D'Haese et al 2019). Previous studies have used lanthanum modified biochar from various sources like rice straw (Dai et al 2014), bamboo (Liu et al 2019), and oak (Wang et al 2015) for phosphate removal, and the highest adsorption capacity was observed to be 142.70 mg/g. Moreover, lanthanummodified biochar obtained from walnut shell showed slight fluctuation and decrease in the adsorption of phosphate in the pH range of 3-11, but as a whole maintained high adsorption capacity over the entire pH range; the phosphate adsorption by lanthanum-modified biochar obtained from mesoporous rice husk was unaffected by the change of pH within a wide pH range of 3-10 ( Tang et al 2019).…”
Section: Introductionmentioning
confidence: 99%